Comparative in vitro Activity of Thiamphenicol-glycinate and Thiamphenicol-glycinate-acetyl-cysteinate and Other Antimicrobials against Respiratory Pathogens - Drago, Lorenzo; De Vecchi, Elena; Fassina, Maria Cristina; Mombelli, Barbara; Tocalli, Loredana; Gismondo, Maria Rita (Arzneimittelforschung, 2001)
Thiamphenicol-glycinate-acetylcysteinate (TGA; CAS 20192-91-0) is widely used for the treatment of infections of varied aetiology. The aim of this study was to compare the antibacterial activity of thiam-phenicol-glycinate (TG; CAS 15318-45-3), TGA, amoxicillin (CAS 61336-70-7) plus clavulanic acid (CAS 58001-44-8), azithro-mycin (CAS 83905-01-5) and ceftriaxone (CAS 104376-79-6). Minimum inhibitory concentrations (MICs) and minimum bactericidal concentrations (MBCs) were determined against Staphylococcus au-reus, Klebsiella pneumoniae, Streptococcus pyogenes, Streptococcus pneumoniae, Moraxella catarrhalis and Haemophilus influenzae according to the National Committee for Clinical Laboratory Standards (NCCLS) methods. The effects of changes in assay conditions were also examined. The activity of TG and TGA was similar to that of amoxicillin plus clavul-anic acid, with the exception of methicil-lin resistant S. aureus. Azithromycin and ceftriaxone were characterised by a limited activity against gram-positive cocci and methicillin resistant and cefinase-positive S. aureus, respectively. TG and TGA are characterized by a wide spectrum of activity, comparable to that of recent commercialized antibiotics for treatment of respiratory tract infections.
Keywords: Amoxicillin plus clavulanic acid; Antimicrobials; Azithromycin; Ceftriaxone; Clavulanic acid; Thiamphenicol-glycinate; Thiamphenicol-glycinate-acetylcysteinate